2021
DOI: 10.1159/000516315
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Focal and Opportunistic Sampling Methods when Studying Chimpanzee Facial and Gestural Communication

Abstract: Researchers frequently use focal individual sampling to study primate communication. Recent studies of primate gestures have shown that opportunistic sampling offers benefits not found in focal individual sampling, such as the collection of larger sample sizes. What is not known is whether the opportunistic method is biased towards certain signal types or signalers. Our goal was to assess the validity of the opportunistic method by comparing focal individual sampling to opportunistic sampling of facial and ges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The opportunistic sampling method resulted in 84.5 hr of video footage. We combined data across the two methods since our previous comparison of the sampling methods showed that they performed similarly (B. N. Florkiewicz & Campbell, 2021). When combined, these sampling methods resulted in 156.5 hr of footage for chimpanzees.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The opportunistic sampling method resulted in 84.5 hr of video footage. We combined data across the two methods since our previous comparison of the sampling methods showed that they performed similarly (B. N. Florkiewicz & Campbell, 2021). When combined, these sampling methods resulted in 156.5 hr of footage for chimpanzees.…”
Section: Methodsmentioning
confidence: 99%
“…We collected data Monday through Friday from 8:00 to 14:00, which we identified as peak activity hours during a pilot study in 2016. We used two different sampling methods to gather our data: the focal individual sampling method (which took place in 2017; Altmann, 1974) and the opportunistic sampling method (which took place from 2018 to 2019; B. N. Florkiewicz & Campbell, 2021). For the focal individual sampling method, we recorded each troop member in 30-min intervals, with each individual sampled once per week.…”
Section: Data Collection With Chimpanzeesmentioning
confidence: 99%
“…As only adult males were focal individuals, there was a greater likelihood of observing a wider range of signals from that demographic group, along with a sampling bias for other chimpanzees who associated with focal males more often during the study period. A mixed-methods approach can also prove valuable in increasing data collection, as a complement of focal and opportunistic sampling increases detection of communicative interactions involving more individuals within the community (Florkiewicz & Campbell, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Data written and recorded with a Canon Vixia HF R800 camera were coded according to the same repertoires, described in Appendix A, Tables 4-6. Adult males were the sole subjects of systematic focal follows, as per the FSCP protocol to not over-habituate adult females at risk of being targeted for the pet trade , and opportunistic data was collected for communicative interactions involving adult females, adolescents, juveniles, and infants within the focal male's current party (Florkiewicz & Campbell, 2021). Individual observation hours (presented in Table 1) were calculated as the time during which each chimpanzee was visible to the researcher as either the focal male or within his party during these contact hours, and observed signals per contact hours were calculated as the frequency of vocal, gestural, and combined signals produced and received divided by the total observation hours for each individual.…”
Section: Data Collectionmentioning
confidence: 99%